3x+4(x-6)+3=0

Simple and best practice solution for 3x+4(x-6)+3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+4(x-6)+3=0 equation:


Simplifying
3x + 4(x + -6) + 3 = 0

Reorder the terms:
3x + 4(-6 + x) + 3 = 0
3x + (-6 * 4 + x * 4) + 3 = 0
3x + (-24 + 4x) + 3 = 0

Reorder the terms:
-24 + 3 + 3x + 4x = 0

Combine like terms: -24 + 3 = -21
-21 + 3x + 4x = 0

Combine like terms: 3x + 4x = 7x
-21 + 7x = 0

Solving
-21 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 7x = 0 + 21

Combine like terms: -21 + 21 = 0
0 + 7x = 0 + 21
7x = 0 + 21

Combine like terms: 0 + 21 = 21
7x = 21

Divide each side by '7'.
x = 3

Simplifying
x = 3

See similar equations:

| 5/x^3(3x^8) | | x+(17x-18)=90 | | 3p+5=11+2p | | 6m^3+54m^2-6m=0 | | 4n-9=5+3n | | .25q+0.10(2q+6)=7.35 | | p+16p-15=0 | | 5(x-1)-2(x+2)=3 | | 5(4-2c)+3(c+9)=12 | | 4x/5-x/1=x/10-6/2 | | x+(7x-18)=90 | | 4x-2=12x-38 | | 3(1x+2)=1/4 | | p(x)=4x^3+6x^2-22x-12 | | 3(x-1)+5(x+1)=18 | | 8+5(s-2t)= | | 2(4)=4x | | 2(2)=4x | | 2(0)=4x | | 35000.00+1680.00x=300440.00 | | 2(-2)=4x | | w+0.12w=17.36 | | (2)=6-2x | | 2/3t+8=6 | | (0)=6-2x | | 2(2n+3)= | | (-2)=6-2x | | 4x+4(-2x-2)=-5-7x | | w+.12x=17.36 | | -(x-1)= | | (2)=2x-2 | | (0)=2x-2 |

Equations solver categories